Distorsi Kajian Hadis: Analisis Fenomena Halusinasi Artificial Intelligence (AI) Dalam Studi Hadis - Muhammad Taufiqqulhidayah Nur Waarits; Via Nur Karima (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
Hadith studies, as the second pillar of Islamic jurisprudence, are fundamentally anchored in the strict principles of authenticity and precision regarding sanad (chain of narration) and matan (text) data. While generative Artificial Intelligence (AI) offers efficiency, it introduces a critical methodological vulnerability known as